Factors associated with Chinese herbal medicine use among middle-aged and older women with arthritis: evidence from China - Lu Yang; David Sibbritt (Scientific Reports, 2022)
Abstract Chinese herbal medicine (CHM) has been used for arthritis in China and elsewhere across the world. However, knowledge about the prevalence and profile of middle-aged and older women who used CHM for arthritis in China is limited. This study aims to identify potentially important insights into the factors associated with CHM use amongst middle-aged and older women with arthritis in China. Data were drawn from the China Health and Retirement Longitudinal Study (CHARLS), a population-based survey of Chinese adults aged 45 years or older, comprising 10,833 Chinese women who completed a questionnaire in 2015. Stepwise multiple logistic regression modeling was conducted to determine the key factors (demographic, health condition, and health services use) predicting the use of CHM for the treatment of arthritis. Results revealed that 17.2% of women with arthritis were taking CHM for their arthritic symptoms. Women with arthritis who used CHM were more likely to experience finger pain (OR = 1.70), had difficulty in stooping, kneeling, crouching (OR = 1.40), visited a Traditional Chinese hospital (OR = 2.22), consulted massage therapists (OR = 2.06) and/or had experienced a fall (OR = 1.41). The prevalence of CHM use is high amongst middle-aged and older Chinese women with arthritis. Given the high risk of functional disability and impaired mental health, further research is needed to explore the potential health benefits of CHM for women with arthritis in order to help facilitate the efficacious and safe use of CHM alongside conventional medical care.